Students' First-Aid Ability in Earthquake Disasters Significantly Improved Through an Online Role-Playing Method - Taukhid, Muhammad; Hayati, Farida; Tri Alfiana, Yolanda (Chakra Brahmanda Lentera Institute, 2021)
Background: The earthquake brought about unprecedented societal changes, particularly among schoolchildren. Thus, in the educational setting, a lack of disaster readiness is caused by a lack of knowledge of hazards, which leads to a lack of preparedness in the event of a disaster. This study aims to see how the role-playing method in the network affects adolescent red cross students' abilities to provide first aid in an earthquake emergency. Methods: The research design used a pre-experimental design with a one-group pre-test post-test design approach to 20 PMR student respondents utilizing the Total Sampling technique, with the intervention of delivering earthquake first aid education, given twice for one week for a total of 60 minutes. An observation sheet was employed as the data-gathering equipment. The data was analyzed. T-Test with paired samples. Results: The results revealed that all respondents with a percentage (100.0 percent) had a 50 percent ability score in the pre-test and practically all of them with a percentage (90.0 percent) had a score of 75 percent-100 percent in the post-test. The mean pre-test = 8.70% and the mean post-test = 27.30% in obtaining value 0,000 = 0.05, indicating that there is an Effect of Method Role Playing In First Aid Network Capability Against Earthquake In PMR students in SMPN 1 Kalidawir Tulungagung. Conclusion: The network's role-playing strategy has an impact on motivation, and motivation is vital in the effectiveness of disaster awareness learning so that the community is more prepared and resilient in the event of a disaster.